High prevalence of azole resistance among environmental Aspergillus fumigatus isolates from outdoor air in Madrid, Spain - Soto-Debrán, Juan Carlos; Sánchez-Íñigo, Francisco Javier; Calvo-López, Alejandro B.; Alguacil-Cuéllar, Laura; Hrynzovska, Anastasiia A.; Mellado, Emilia; García Dos Santos, Saul; Alcazar-Fuoli, Laura; Alastruey-Izquierdo, Ana (Frontiers in Microbiology, 2026)
IntroductionAspergillus fumigatus has been designated by the World Health Organization (WHO) as a critical fungal pathogen. Its spores are commonly present in the air and are inhaled daily. Azoles are the first-line treatment for Aspergillus infections, but the emergence of resistance is a growing concern. However, limited data exist on the occurrence of azole-resistant A. fumigatus in the outdoor environment in Spain.MethodsThis study aimed to investigate the prevalence of azole-resistant A. fumigatus isolates in outdoor air at two distinct locations in Madrid. We characterized the isolates using TRESPERG genotyping and examined the underlying molecular mechanisms responsible for azole resistance development.ResultsAzole-resistant A. fumigatus isolates were found in 55% of the 20 air samples collected. Among the 200 A. fumigatus isolates analyzed, 38.5% were azole resistant and were classified into 10 different genotypes. Notably, the TR34/L98H mutation in Cyp51A was found in 77% of the resistant isolates, while 23% showed no mutations in the screened targets (cyp51A, cyp51B, or hmg1).DiscussionThis study revealed a high prevalence of azole-resistant A. fumigatus in outdoor environmental air, with the TR34/L98H mutation being the main mechanism of azole resistance. A close genetic relationship was observed among the resistant isolates. This research underscores the need for continued monitoring of environmental azole-resistant A. fumigatus isolates and highlights the importance of understanding genetic diversity and resistance mechanisms to develop effective strategies for fungal infection control.